The effect of training, work climate, and work stress on employee productivity of bank DBS Imam Bonjol branch Medan - Megasari Megasari; Purnama Yanti Purba; Alprima Abner Daniel Putra Lubis; Muhammad Munir Siregar (Institute of Computer Science (IOCS), 2023)
This study aims to explain the effect of training, work climate and work stress on the productivity of DBS bank employees. The phenomenon of decreased employee productivity is characterized by targets not being achieved, ineffective training, excessive workload and an unfavorable organizational climate at DBS Imam Bonjol bank are the background of this research. This type of research is descriptive quantitative. The sampling technique uses a saturated sample. The number of samples is 101 employees. The data analysis method is multiple linear regression. The research results show that partially Training has a positive and significant effect on Employee Productivity, Work Climate has a positive and significant effect on Employee Productivity, Work Stress has a negative and significant effect on Employee Productivity of DBS Bank Imam Bonjol Branch Medan. Simultaneously Training, Work Climate and Work Stress have a significant and positive effect on Employee Productivity of DBS Bank Imam Bonjol Branch Medan.